2015
DOI: 10.1002/srin.201400612
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Limestone in Hot Metal at 1300 °C

Abstract: Decomposition and dissolution of cylindrical limestone samples (ø16 mm  50 mm approximately) in hot metal at 1300 8C are experimentally studied. The cross section of burned limestone is determined by using image processing and then the lime layer thickness is determined. The three layers of the cross section of burned sample are analyzed by using SEM, and the change of the Fe content along the radial direction is also analyzed. A kinetic model is established to characterize the calcination of limestone in hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…But with the increase of temperature, especially limestone is used to add into the converter as slagging agent, and the temperature of early converter steelmaking is above 1250°C, which is much higher than the critical temperature of limestone decomposition, limestone decomposition pressure can reach about 40 atmospheres, leading to that the diffusion of CO 2 gas driven by concentration gradient may not be the main factor for the mass transfer of CO 2 outwards. In a previous work by the present authors, it has been preliminarily determined that heat transfer is the controlling step for the limestone decomposition in hot metal at 1300°C [21]. In this paper, the detailed kinetics of limestone decomposition in hot metal under different conditions, such as temperature of hot metal and rotating speed of cylindrical limestone samples, are further studied.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…But with the increase of temperature, especially limestone is used to add into the converter as slagging agent, and the temperature of early converter steelmaking is above 1250°C, which is much higher than the critical temperature of limestone decomposition, limestone decomposition pressure can reach about 40 atmospheres, leading to that the diffusion of CO 2 gas driven by concentration gradient may not be the main factor for the mass transfer of CO 2 outwards. In a previous work by the present authors, it has been preliminarily determined that heat transfer is the controlling step for the limestone decomposition in hot metal at 1300°C [21]. In this paper, the detailed kinetics of limestone decomposition in hot metal under different conditions, such as temperature of hot metal and rotating speed of cylindrical limestone samples, are further studied.…”
Section: Introductionmentioning
confidence: 91%
“…This process can be approximately considered as the gas is driven by pressure gradient through the fixed bed layer, and the model is established to analyse the process. The form of unreacted limestone (CaCO 3 ) of limestone inside is still the roundness for the cylindrical limestone after calcination, and the outer ring is lime (CaO) of reaction product layer, unreacted limestone layer and lime layer form the shape of concentric round regularly [21]. The process of the diffusion of CO 2 gas from the interface of CaCO 3 /CaO is considered as the main research object.…”
Section: Model Of Mass Transfer Control Driven By Pressure Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…Li 2 O and Na 2 O tend to restrain the crystallization of nonreactive mold fluxes by lowering the initial crystallization temperature and increasing incubation time. [82][83][84][85] When mold fluxes contain no Na 2 O, the crystallization ratio is lower than that of the mold flux with high Na 2 O and high Li 2 O. Therefore, CaO-Al 2 O 3 -based mold fluxes with no Na 2 O and high Li 2 O have appropriate crystallization ability, which is helpful for improving lubrication.…”
Section: Mold Fluxes With Low Sio 2 Contentmentioning
confidence: 99%
“…Compared with the conventional lime steelmaking process, the dissolution of limestone is accompanied by the decomposition reaction of limestone in the limestone steelmaking process. The decomposition of limestone in converter slag is a strong endothermic reaction which has been studied by many researchers [13][14][15]. Deng et al [16] studied the dissolution of limestone in slag at 1600°C and concluded that the structure of the decomposed limestone became very dense at the boundary, resulting in a dense CaO layer at the surface of the generated lime.…”
Section: Introductionmentioning
confidence: 99%